2013
DOI: 10.1111/j.1467-8489.2012.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

El Niño southern oscillation and its effects on world vegetable oil prices: assessing asymmetries using smooth transition models

Abstract: In this research, we examine the effects of El Niño southern oscillation (ENSO) on market dynamics of major vegetable oil prices. We adopt a smooth transition vector error correction modelling framework to analyse the impacts of ENSO events on the vegetable oil prices and, more interestingly, to investigate the asymmetric nature of the ENSO dynamics and price responses to ENSO shocks. The results confirm selfexciting type nonlinearities in the ENSO dynamics, and presence of the so-called transactions cost band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 45 publications
2
40
1
2
Order By: Relevance
“…Such asymmetrical relationships highlight that the strength of El Niño years exerts a much greater influence on Thailand's rice production, area harvested and yield than the magnitude of La Niña years does. The results from this analysis are in line with the studies of Ubilawa (2012) and Ubilawa and Holt (2013) demonstrating that El Niño and La Niña events exerted asymmetric effects on wheat yields, prices, stock-to-use ratios and exports for all export countries. Gutierrez (2017) also showed that La Niña exerted, on average, a stronger and negative impact on wheat yield anomalies, exports and stock-to-use ratios than El Niño.…”
Section: Asymmetrical Relationships Between Enso Index and Thailand'ssupporting
confidence: 87%
“…Such asymmetrical relationships highlight that the strength of El Niño years exerts a much greater influence on Thailand's rice production, area harvested and yield than the magnitude of La Niña years does. The results from this analysis are in line with the studies of Ubilawa (2012) and Ubilawa and Holt (2013) demonstrating that El Niño and La Niña events exerted asymmetric effects on wheat yields, prices, stock-to-use ratios and exports for all export countries. Gutierrez (2017) also showed that La Niña exerted, on average, a stronger and negative impact on wheat yield anomalies, exports and stock-to-use ratios than El Niño.…”
Section: Asymmetrical Relationships Between Enso Index and Thailand'ssupporting
confidence: 87%
“…Therefore, these price shocks will eventually impact the demands for close substitutes such as soybean oil or sunflower oil. Ubilava and Holt () and Liao et al . () found that El Niño has a negative effect on soybean futures prices while La Niña has the opposite effect.…”
Section: Incorporating Exogenous Drivers Of Volatilitymentioning
confidence: 99%
“…For example, the increasing temperatures and sunlight and decreasing rainfalls prompt coffee plants growth which has a beneficial influence (Ubilava, 2012a andBastianin, Lanza, andManera, 2018). As reported by Ubilava, 2013, El Niño reduces wheat, corn and soybeans prices in the international market and those goods are imported by Colombia which could help reduce inflationary pressures during a strong El Niño.…”
Section: Enso and Its Relationship With The Colombian Economymentioning
confidence: 96%
“…On the economic framework, Hall, Skalin, and Teräsvirta, 2001 identify disparities in the autocorrelation functions patterns which reflect ENSO asymmetries between El Niño and La Niña phases. Supporting this idea, Ubilava and Holt, 2013 state an improvement in performance modeling of commodity price forecasts by using nonlinear smooth Nonlinear relationship between the weather phenomenon El Niño and Colombian food prices transition models compared to the traditional lineal models.…”
Section: Introductionmentioning
confidence: 99%